Simulation-Assisted Determination of the Minimum Melting Temperature Composition of MgCl2–KCl–NaCl Salt Mixture for Next-Generation Molten Salt Thermal Energy Storage - Villada, Carolina; Ding, Wenjin; Bonk, Alexander; Bauer, Thomas (Frontiers in Energy Research, 2022)
Molten chloride mixtures such as MgCl2-KCl-NaCl are potential thermal energy storage (TES) materials for next-generation concentrating solar power (CSP) systems due to their high operation temperature (> 700 °C) and low costs. This ternary MgCl2-KCl-NaCl salt mixture with a low material cost (< 0.35 /kg) is a promising salt for high-temperature TES applications, e.g., it could enable next-generation CSP plants to have significantly lower levelized costs of electricity (LCOE). In this work, the minimum-melting-temperature composition for the MgCl2-KCl-NaCl mixture was estimated by FactSage simulation, while the binary and ternary phase diagrams of the MgCl2-KCl-NaCl salt system including their phase transitions were studied. Five different eutectic compositions of the MgCl2-KCl-NaCl mixture from literature and simulations were selected to determine the minimum-melting-temperature composition by the Differential Scanning Calorimetry technique. Results show agreement between experiments and simulations of the melting temperature and its composition. Hence, values of the exact and reliable minimum melting temperature and salt composition in mol. % and wt. % are given. Based on the determined melting temperature, the minimum operating temperature of MgCl2-KCl-NaCl is recommended according to safety margin for CSP applications.